Positive Discrimination inFavor of Women in Job Leave and itsImpact on Family Protection - Latif, Shailan Rauf (Journal of Legal and Political Studies, 2018)
Citizens equality in law is a constitutional principle, most of the modern constitutions mentioned this principle, and the Constitution of the Republic of Iraq for 2005, also took this direction. But genders equality cannot be achieved in an absolute way and in every situation without taking social circumstances of both genders to consideration, for example the state's commitment in motherhood protecting issue and protecting child from this way, behaving females, mothers in other words, sometimes needed to be different from that of males, fathers in other words. When we deal with employee's equality in public employment, we find somehow inequality between male and female employees whom they have got married in "leave of absence" issue, as one of the employee's rights. This kind of discrimination can be considered as a positive discrimination and has benefit for protecting family and children. From this way we can achieve public interest of community because family is the base of community, so protecting family means protecting the whole community.
Keywords: Citizens equality; modern constitutions; motherhood; employees equality; public employement